Information technology. International standardized profile TAnnnn. Connection-mode transport service over connectionless-mode network service. TA51 profile including subnetwork-dependent requirements for CSMA/CD Local area networks (LANs) Part 2, (15th November 1995) - British Standards Institution
No abstract available